STAFF INTERACTION AND SCHOOL INNOVATIVENESS IN WESTERN NIGERIA SECONDARY SCHOOLS (1975)
The main purpose of this study is to determine the extent to which the interpersonal relationships among teachers in our secondary schools help or hinder the introduction of educational innovative practices in the direction of encouraging vocational and practical subjects in Nigeria's secondary school curriculum. 557 teachers (these include 30 principals and over 40 heads of departments) were involved in the survey. All the subjects have taught for, at least, six months prior to the period of the survey in the schools that participated. The findings of the study showed 1. that for the total sample of schools used in this study there is no significant relationship between staff interaction and school innovativeness, talking generally. There are however specific identifiable patterns: (i) schools with low staff interaction and low degree of innovativeness (2) schools with high staff interaction and high degree of innovativeness. 2. There is significant difference in the degree of Staff interaction among all-boys, all-girls and co-educational schools. 3. There is no significant relationship between the Personality variables of principals (age and teaching experience) and the degree of staff interaction. 4. There is no significant relationship between the personality variables of teachers (age and teaching experience) and the degree of staff interaction. 5. The Personality variables of principals (age and teaching experience) are not significantly related to the degree of school innovativeness. 6. The personality variables of teachers (age and teaching experience) are not significantly related to the degree of school innovativeness. The study has implications for Nigeria’s educational System. These include the need for the introduction of a comprehensive secondary school system and the evolvement of new teacher education programmes in the country.